Clinical Outcomes Associated With Induction Regimens Among Retransplant Kidney Recipients in the United States. Issue 6 (June 2015) - Schold, Jesse; Poggio, Emilio; Goldfarb, David; Kayler, Liise; Flechner, Stuart
<x xml:space="preserve">Abstract</x> Background Numerous studies have evaluated outcomes and risk factors associated with induction protocols among kidney transplant recipients. However, few studies have evaluated outcomes in the subset of retransplant recipients who often have unique immunologic condition and risk profile and represent an increasing proportion of transplant patients in the United States. Methods We evaluated the association of common induction treatments (alemtuzumab, thymoglobulin, interleukin-2 receptor blockers, and no induction) given at transplantation with clinical outcomes among adult recipients retransplant between 2003 and 2011 using national Scientific Registry of Transplant Recipients data (n = 14, 336). We used a propensity score analysis to minimize potential selection biases for allocation of treatment. Results In adjusted models, there were no significant differences between induction groups for outcomes of delayed graft function, 1-year acute rejection, 1-year BK virus or patient death. Acute rejection before hospital discharge was lowest among patients treated with thymoglobulin and alemtuzumab. The no induction group had the highest average 1-year estimated glomerular filtration rate (62 mL/min/1.73kg/m2) and lowest incidence of any malignancies within 1 year (1.0%). Hospitalizations after transplantation were highest among patients treated with thymoglobulin (42% at 1 year). Recipients with alemtuzumab had the highest relative risk for graft loss (adjusted hazard ratio, 1.19; 95% confidence interval, 1.01–1.40, relative to patients treated with thymoglobulin). Conclusion There is moderate variation in clinical outcomes associated with induction treatment among retransplant kidney recipients in the United States, including higher graft loss rates among recipients treated with alemtuzumab but similar patient survival between all regimens.